2015
DOI: 10.5194/isprsarchives-xl-5-w4-345-2015
|View full text |Cite
|
Sign up to set email alerts
|

Bim From Laser Clouds and Finite Element Analysis: Combining Structural Analysis and Geometric Complexity

Abstract: ABSTRACT:This paper describes the use of BIM models derived from point clouds for structural simulation based on Finite Element Analysis (FEA). Although BIM interoperability has reached a significant level of maturity, the density of laser point clouds provides very detailed BIM models that cannot directly be used in FEA software. The rationalization of the BIM towards a new finite element model is not a simple reduction of the number of nodes. The interconnections between the different elements and their mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 10 publications
1
42
0
Order By: Relevance
“…Processing high density point clouds, derived both from photogrammetric and laser scanning surveys (Oreni et al, 2014), it's possible to produce very detailed BIM models. However, there is still the lack of complete algorithms able to perform an automated processing from point clouds to structural simulation based on FEM (Barazzetti et al, 2015). In another application, a validation for models reconstructed from point clouds, restricted to façades, was carried out .…”
Section: Point Clouds Managementmentioning
confidence: 99%
“…Processing high density point clouds, derived both from photogrammetric and laser scanning surveys (Oreni et al, 2014), it's possible to produce very detailed BIM models. However, there is still the lack of complete algorithms able to perform an automated processing from point clouds to structural simulation based on FEM (Barazzetti et al, 2015). In another application, a validation for models reconstructed from point clouds, restricted to façades, was carried out .…”
Section: Point Clouds Managementmentioning
confidence: 99%
“…A lot of developments for as-built BIM are emerging from the adoption of BIM from cultural heritage communities. Many authors have shown the benefits of using BIM for cultural heritage preservation (Fai et al, 2011, Oreni et al, 2014, Wu et al, 2013, Boeykens et al, 2012, Pauwels et al, 2008, Quattrini et al, 2015, Barazzetti et al, 2015. Pauwels et al (2008) describe an approach called Architectural Information Modelling which uses BIM to document geometric data along with appended historical information such as photographs, scanned documents or research material.…”
Section: As-built Bimmentioning
confidence: 99%
“…In fact for the parametric modelling of CH, the control of LoD (Level of Development), the structural elements complexity level and the predetermined discretization of the model is fundamental (Barazzetti et al, 2015a). The BIM interoperability needs are addressed with the IFC standards (Industry Foundation Classes) BuildingSMART that is all about the sharing of information between project team members and across the software applications.…”
Section: * Corresponding Authormentioning
confidence: 99%